Fun, 'Family', and Friends: Developing pro-environmental behaviour among high school students in Indonesia. Issue 136 (2nd September 2018) - Tanu, Danau; Parker, Lyn
ABSTRACT: This article explores a unique form of environmental education (EE) being implemented in schools in Surabaya, Indonesia. An environmental NGO (TENGO) and the national in-school programme, Adiwiyata, attract students to engage in pro-environment activities such as making compost and rehabilitating mangroves. Ethnographic research in and around high schools revealed that these activities entail a very deliberate construction of a group identity, which has at its heart the ethos of kekeluargaan (family-togetherness). Students join the club because of this feeling of belonging to a 'family' of friends and have a huge amount of fun doing environmental activities together. The article shows the affective appeal to young people: as a social club that runs physically engaging activities, the role of humour, and the transgressive appeal of 'daring to be dirty'. The 'learning by doing' programme run by TENGO circumvents the institutional apathy and lack of capacity to implement formal EE in class. Although Surabaya is becoming 'clean and green', partly through the hard work of students, the activities neglect learning about complex, human–environment interactions, as in more conventional EE. So, is it environmental education, and will individuals continue 'being green' after they leave school?